Mechanical performance of aluminum/copper/aluminum nanocomposite at different temperatures using molecular dynamics simulation - Narinderjit Singh Sawaran Singh; Ali B.M. Ali; Shahram Babadoust; Rasha Abed Hussein; Soheil Salahshour; Sh. Baghaei; S. Mohammad Sajadi (Composites Part C: Open Access)
With the expansion of science and technology, the application and importance of composites in various industries increased. Aluminum /copper metal layer composites are widely used for their fracture toughness, corrosion resistance, and high electrical conductivity. This research simulated an Aluminum /copper/Aluminum tri-layer nanocomposite to investigate the effects of different temperatures (T = 300, 350, 375, 400, 450, and 500 K) on its mechanical properties. The stress, strain rate, yield strength, and ultimate strength values were recorded. The results indicate that the physical stability of the sample remained unaffected as temperature increased, while the attraction force among different particles was observed. Furthermore, the simulation results suggest that the mechanical strength of aluminum/copper/aluminum tri-layer nanocomposite decreased with rising initial temperature in the computational box. Specifically, the ultimate strength and Young's modulus of nanocomposites reduced to 2.186 GPa and 12.727 GPa, respectively, at 500 K. Aluminum /copper/Aluminum tri-layer nanocomposite showed promising potential for real-world applications, particularly in sectors requiring materials with enhanced mechanical properties. It is expected that these composites will be utilized in advanced engineering fields, such as aerospace and automotive industries, where their high strength-to-weight ratio and thermal stability can significantly improve performance and efficiency.